Evaluation of mode of birth in pregnant women with heart disease. (May 2020) - Petrus, Annelieke H.J.; Jongert, Britt L.; Kiès, Philippine; Sueters, Marieke; Jongbloed, Monique R.M.; Vliegen, Hubert W.; Schalij, Martin J.; van Lith, Jan; van den Akker, Thomas
Abstract: Objective: Maternal heart disease (HD) complicates 1–4 % of pregnancies and is associated with adverse maternal and fetal outcomes. Although vaginal birth is generally recommended in the guidelines, cesarean section (CS) rates in women with HD are often high. Aim of the present study was to evaluate mode of birth and pregnancy outcomes in women with HD in a tertiary care hospital in the Netherlands. Study design: The study population consisted of 128 consecutive pregnancies in 99 women with HD, managed by a pregnancy heart team between 2012–2017 and ending in births after 24 weeks' gestation. Pregnancy risk was assessed per modified World Health Organization class. Mode of birth (planned and performed) and maternal and fetal complications (cardiovascular events, postpartum hemorrhage, prematurity, small for gestational age and death) were assessed for each pregnancy. Results: Pregnancy risk was classified as modified World Health Organization class I in 23 %, class II in 50 %, class III in 21 % and class IV in 6% of pregnancies. Planned mode of birth was vaginal in 114 pregnancies (89 %) and CS in 14 (11 %; nine for obstetric and five for cardiac indication). An unplanned CS was performed in 18 pregnancies (16 %; 16 for obstetric and two for cardiac indications). Overall mode of birth was vaginal in 75 % and CS in 25 %. Twelve cardiovascular events occurred in eight pregnancies (6 %), postpartum hemorrhage in nine (7 %) and small for gestational age in 14 (11 %). No maternal or fetal deaths occurred. Conclusions: Findings of this study indicate that – given that pregnancies are managed and mode of birth is meticulously planned by a multidisciplinary pregnancy heart team – vaginal birth is a suitable option for women with HD.